Microstructure and Mechanical Properties of Compact SiC/SiC Composite Fabricated with an Infiltrative Liquid Precursor. Issue 4 (6th January 2015) - Zhao, Shuang; Yang, Zichun; Zhou, Xingui; Besmann, T.
<x xml:space="preserve">Abstract</x> Continuous SiC fiber reinforced SiC matrix composites (SiC/SiC) have been studied and developed for high temperature and fusion applications. In this study, SiC/SiC composite was fabricated by polymer impregnation and pyrolysis process with LPVCS, a liquid precursor with active Si–H and ‐CH=CH2 groups. The cross‐link and ceramization processes of LPVCS were studied and SiC/SiC composite was fabricated with LPVCS. The porosity and mechanical properties of the SiC/SiC composite was investigated, and the results indicated that the SiC/SiC composite exhibited low porosity and superior mechanical properties owing to the compact matrix derived from LPVCS.